Treatment of a Prader-Willi Patient with Recurrent Catatonia - Hana M. Poser; Alexandru E. Trutia (Case Reports in Psychiatry)
Prader-Willi is a genetic disorder characterized by neonatal hypotonia, hyperphagia, short stature, hypogonadism, and mental delay. This disorder can result from multiple mechanisms, most commonly a deletion of paternal chromosome 15, leaving a single maternally derived chromosome 15. Individuals who have a maternal uniparental disomy of chromosome 15 have a higher risk for developing psychosis compared to other forms of Prader-Willi. The following report details the treatment course of a 24-year-old female with Prader-Willi and recurrent catatonia. The patient initially had a positive lorazepam challenge test but subsequently failed treatment with benzodiazepines. She then received eight electroconvulsive therapy (ECT) treatments after which she showed improvement from initial catatonic state. However, the resolution in her symptoms did not follow a linear course but would show periods of improvement followed by a return of catatonic features. This case provides an example of the complexity of treatment of a patient with a genetic disorder and recurrent catatonia.